A Robust Baseband Demodulator for ISO 18000-6C RFID Reader Systems. (9th September 2012) - Jin, Cheng; Cho, Sung Ho
Abstract : One key challenge for ultra-high frequency (UHF) radio-frequency identification (RFID) reader design is to demodulate the weak tag response signal which tends to be easily distorted and has considerable frequency deviations. In this paper, a baseband demodulator based on a matched filter (MF) is proposed to enhance the reliability of signal processing for the EPCglobal Class-1 Generation-2 (Gen2) RFID reader systems. The proposed demodulator is very robust against strong signal distortions and large frequency deviations happening on the received backscattered signal from a passive RFID tag. The validity and usefulness is demonstrated by both computer simulations and implementation experiments.